ETANOL DARI UMBI KAYU DAN KARAKTERISASI CAMPURANNYA DENGAN BENSIN SEBAGAI SUBSITUTUSI BENSIN - -, Sukamta; Kustanto, David; Yanto, Tri Nuri (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2010)
The mixture of etanol and gasoline which is called bioetanol could be an alternatif for fuel. An etanol could be made of cassava. This article discusses a further development of ethanol production and its blend with gasoline and its characterization as a fuel. The experimental work was devided into three steps, i.e. material preparation, fermentation, and finally distillation at 80, 95 and 110 0C. The destillitation resulted a 95% ethanol and the conversion of carbohydrate to ethanol was about 93- 98%. The analysis results of the blend of gasoline and ethanol such as kynematic viscosity 100 oF at temperatures of 40 and 60 oC was 8,645 cSt dan 8,151 cSt respectively and the specific grafity at temperatures of 40 and 60 oC 0,7472 dan 0,743 respectively. The flame test of the blending of gasoline: ethanol volume of 9:1 and the 100 % gasoline results showed that the flame of bioethanol (9 :1) was about 39-40 second which was 4-6 second longer than the 100 % gasoline that the flame was about 34-35 second.